Influence of Sexual Hormones on Neural Orofacial Perception. Issue 8 (15th December 2016) - Alves, Bruna; Ibuki, Flavia; Gonçalves, Alyne Simões; Teixeira, Manoel Jacobsen; De Siqueira, Silvia Regina Dowgan Tesseroli
Abstract: Objective. To investigate the trigeminal somatosensory (thermal, pain, tactile, vibratory, and electric), gustative (salty, bitter, sweet, sour), and olfactory thresholds in healthy women during the menstrual cycle and investigate any association with estradiol and progesterone levels in saliva. Methods. We examined/tested 39 women between age 19 and 47 years and with regular menstrual cycles and no comorbidities. All women were informed about the purposes of the study, and only those who signed the informed consent were included. The tests were performed at three stages within the cycle: menstrual phase, follicular phase, and luteal phase. The procedure consisted of saliva collection at the beginning of each session to measure hormone levels, salivary flow, somatosensory evaluation with quantitative sensory testing applied to the right trigeminal maxillary branch and right forearm, gustative (sweet [glucose], salt [sodium chloride], sour [citric acid], and bitter [urea]) and olfactory (isopropanol at different concentrations) thresholds. Results. During the menstrual cycle, thresholds for sweet, salty, sour, cold, vibration, and deep pain decreased, but warmth, electrical, and superficial pain thresholds increased. The bitter threshold was high, and the olfactory threshold was low in the follicular phase. Low estrogen levels were correlated to high deep pain thresholds in the forearm ( P = 0.008) and face ( P = 0.041), high tactile thresholds ( P = 0.001), and high superficial pain ( P = 0.006) thresholds in the face. High levels of progesterone were associated with a high deep pain threshold in the face and a high salty threshold ( P < 0.001). Conclusion. Estrogen and progesterone seem to be involved in sensory neuromodulation in women during the menstrual cycle.